Microgeração e minigeração de energia fotovoltaica distribuída na cidade de São Paulo: oportunidades e desafios - Rodrigues, Fabio Nomachi (2018)
The aim of this research was to analyse the potential and requirements for distributed microgeneration and mini-generation of photovoltaic energy in the city of São Paulo. Photovoltaic energy is the electric energy generated by direct conversion of solar radiation. To convert solar energy into electrical energy, a photovoltaic system composed of photovoltaic panels, inverter and batteries is required. Photovoltaic panels have become popular in recent years and consist of an alternative to energy generation from a renewable and unlimited source, available throughout the planet with affordable cost for both implementation and maintenance and no waste. The recent updates of Brazilian legislation, through the ANEEL normative resolution nº 482/2012 and later update with the ANEEL normative resolution 687/2015, allow ordinary citizens to generate electric energy for their own consumption and direct the surplus of production to the electric grid. This surplus of electrical energy produced from a renewable source is converted into credits that can be used when electricity consumption is higher than production. In the case of photovoltaic solar energy, this occurs at night and on periods of overcast sky during day time. Solar photovoltaic energy is the primary source of energy with more potential to grow in Brazil, as shown in the Brazilian Energetic Balance. However, the conversion of solar radiation in electric energy represents in absolute terms a small fraction of the Brazilian energy matrix. In this context, the aim of this study was to analyse the characteristics and the potential for distributed microgeneration and mini-generation of photovoltaic energy in the city of São Paulo. This exploratory work with a qualitative methodological approach uses the case study as a research strategy, investigating the phenomenon within its real context. The main players involved in distributed photovoltaic generation are the users, the energy distributor and the integrator. For the consumers interviewed, the environmental benefits provided by the installation of a photovoltaic system associated with a medium-term payback are the most important factors for decision-making in the acquisition of this system. Regarding the distributor, it was observed that it has a passive posture for the expansion of photovoltaic energy in the city of São Paulo. The integrator is directly involved with the consumer and the distributor, being responsible for all commercial, technical and bureaucratic intermediation. According to reports from consumers and the energy distributor, the integrators have been doing a satisfactory work. The city of São Paulo has a high potential for photovoltaic energy generation due to the favorable characteristics of solar radiation in the region, which is densely urbanized, and thus has a high number of roofs available for the installation of photovoltaic systems without competing for space with other urban appliances. In addition, one of the country's largest electricity distributors is located in the city of São Paulo. However, the scarcity of public policies and lines of credit with affordable interest rates represent the main challenges for the expansion of distributed photovoltaic energy in the city of São Paulo.